National Business Systems and the Development of Corporate Social Responsibility in Chile - Soos, Eszter (2017)
Today there is increasing pressure for international businesses to take into account their impact in different countries where they are operating and adopt CSR initiatives. However, several authors argue that international firms would not simply impose the same CSR initiatives across different national contexts, but that they would adapt to different nation-level institutions, which can be characterised as national business systems. This paper aims to examine how far the national business system of Chile affects CSR initiatives of businesses operating in Chile using Ioannou and Serafeim’s 2012 framework of the role of nation-level institutions in shaping CSR. This study finds that the national business system of Chile shapes companies’ CSR initiatives to an extent, however CSR is still in its infancy in the country and so it does not play as much of a role in shaping CSR as might be seen in more developed countries.